(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teaching a foreign language for special purposes is an organized process of implementing an educational course for specialists with the aim of developing their foreign language communicative competence in the professional field. The article discusses the issues of teaching a foreign language for special (professional) purposes” in a non-technical university.